Skeleton keys and Trojan horses: a review of therapeutic delivery to the brain - Stoub, Rachel E.; Bailus, Barbara J. (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe advances in genetic medicine that have occurred in the last few decades have been tempered by the challenges in delivering those medicines to the desired organs and cell types. Nowhere has this delivery challenge been greater than in the brain, due to the blood brain barrier (BBB), often illustrated as an impenetrable castle wall. As the need for neurological therapies grows, an assortment of Trojan horse and skeleton key strategies have been designed to allow passage of therapeutics through the BBB, These range from designer viral vectors, to cell penetrating peptides that can target cell surface receptors, to genetically modifying hematopoietic stem cells, to lipid nanoparticles that pass through the cell membrane.ResultsThis review will examine the precise method that each delivery vehicle uses to enter and transverse the endothelial layer of the to BBB and arrive in the brain parenchyma. The advantages and challenges of each delivery strategy will be discussed, as will the most recent clinical trials using these technologies.ConclusionThere are several extremely promising delivery vehicles that are able to cross the BBB and deliver genetic therapies to neuronal cells. Several of these delivery vehicles have already been approved for use in patients. As these delivery vehicles become further optimized there is the potential to treat a majority of neurological disease and disorders.